2007
DOI: 10.1002/hep.21598
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnostic potential for hepatocellular carcinoma using the SELDI ProteinChip system†

Abstract: Early detection of HCC increases the potential for curative treatment and improves survival. To facilitate early detection of HCC, this study sought to identify novel diagnostic markers of HCC using surface-enhanced laser desorption ionization time-of-flight mass spectrometry (SELDI-TOF/MS) ProteinChip technology. Serum samples were obtained from 153 patients with or without HCC, all of whom had been diagnosed with HCV-associated chronic liver disease. To identify proteins associated with HCC, serum samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 65 publications
1
33
0
Order By: Relevance
“…The sera of all patients with and without HCC, which was confirmed by abdominal ultrasonography or computed tomography, were obtained prior to treatment. All of the sera samples from HCV-infected patients were analyzed in a previous study [15]. In addition, sera from 10 HCV-HCC patients who were diagnosed with HCC within 1 or 2 years and sera from five patients who had received radiofrequency ablation (RFA), percutaneous ethanol injection therapy (PEIT) and/or transarterial chemoembolization (TACE) for HCC were collected through a cohort study in Miyazaki.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The sera of all patients with and without HCC, which was confirmed by abdominal ultrasonography or computed tomography, were obtained prior to treatment. All of the sera samples from HCV-infected patients were analyzed in a previous study [15]. In addition, sera from 10 HCV-HCC patients who were diagnosed with HCC within 1 or 2 years and sera from five patients who had received radiofrequency ablation (RFA), percutaneous ethanol injection therapy (PEIT) and/or transarterial chemoembolization (TACE) for HCC were collected through a cohort study in Miyazaki.…”
Section: Samplesmentioning
confidence: 99%
“…Studies using the ProteinChip SELDI system, which is a powerful tool to discover new biomarkers, have shown that this method may be successfully used to diagnose HCC. Zinkin et al [13], Schwegler et al [14] and our research group [15] previously detected early HCC using the profile of several protein peaks that were identified by the ProteinChip SELDI system. Paradis et al [16] reported the highest discriminating peak (8900 Da), which was identified as the V10 fragment of vitronectin.…”
Section: Introductionmentioning
confidence: 98%
“…We searched the serum proteome of astrocytoma patients and control subjects using SELDI-TOF mass spectrometry (MS), which has successfully identified serum biomarkers in other forms of cancer (5,6 ) and infection (7 ). A major advantage of SELDI-TOF MS is that it makes no a priori assumptions about the nature of biomarkers.…”
Section: © 2008 American Association For Clinical Chemistrymentioning
confidence: 99%
“…A comprehensive protein analysis using the ProteinChip SELDI system was performed as previously described (16,17) under the following conditions, in which several protein signals can be obtained in a stable manner. Native serum was applied to a hydrophobic cationexchange chip (CM10, Bio-Rad Laboratories, Hercules, CA, USA).…”
Section: Clinical Characteristics In Patients With Iga Nephropathymentioning
confidence: 99%